2020
DOI: 10.1080/07315724.2020.1737985
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Interprofessional Nutrition Workshop to Integrate Nutrition Education into a Preclinical Medical School Curriculum

Abstract: Objective: The patient-physician encounter provides an ideal opportunity to assess a patient's dietary history and its impact on total health. However, nutrition assessments and counseling in physician-patient encounters is often lacking. Insufficient nutrition education during medical school may lead to insecurity in assessing and counseling patients. Methods: Physicians and registered dietitians (RD) co-developed and co-facilitated a nutrition workshop for first-year medical students. Goals included increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Prior to attending the Nutrients 2021, 13, 4081 6 of 8 nutrition workshop, only half of our medical students felt that they had sufficient medical knowledge to counsel a patient on nutritional matters, and only a third felt comfortable in completing a nutritional assessment. After the first workshop, students reported that they had adequate knowledge to counsel a patient on nutrition matters, felt comfortable completing a nutrition assessment, and felt confident advising patients about nutrition, which is consistent with our previous findings [12].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Prior to attending the Nutrients 2021, 13, 4081 6 of 8 nutrition workshop, only half of our medical students felt that they had sufficient medical knowledge to counsel a patient on nutritional matters, and only a third felt comfortable in completing a nutritional assessment. After the first workshop, students reported that they had adequate knowledge to counsel a patient on nutrition matters, felt comfortable completing a nutrition assessment, and felt confident advising patients about nutrition, which is consistent with our previous findings [12].…”
Section: Discussionsupporting
confidence: 88%
“…Enhancing confidence is crucial, as it breaks down the insecurity barrier preventing students counseling patients on nutrition and increases their self-efficacy. The design of our workshop was structured similarly to a previous nutrition workshop carried out at ZSOM and aligns with the American Nutrition Association's personalized nutrition model [12,20]. Our workshops helped to integrate the basic science and clinical concepts taught in the existing curriculum using realistic and common patient presentations as the context for learning nutrition concepts and practicing important skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations